New syllabus primary mathematics 5 - Yee, Dr. Foong Pui (Karachi: Oxford University Press., 2024)
New Syllabus Primary Mathematics 5 is a comprehensive textbook designed to advance students' understanding of key mathematical concepts at the Grade 5 level. The book covers topics such as whole numbers, fractions, decimals, percentages, geometry, measurement, and basic algebra. Through clear explanations, step-by-step examples, and interactive activities, the textbook promotes critical thinking and problem-solving skills. Each chapter includes exercises to reinforce learning and real-world applications to help students connect mathematical theories to everyday situations. This textbook serves as a solid foundation, preparing students for more advanced mathematics in higher grades.